Effects of wheat straw application on methane and nitrous oxide emissions from purplish paddy fields - Y. Wang; C. Hu; B. Zhu; H. Xiang; X. He (Plant, Soil and Environment, 2010)
Little information has been known on greenhouse gas emissions from the unique purplish farmland that produces rice for more than 100 million people in Southwest China. We studied methane (CH4) and nitrous oxide (N2O) emissions under four wheat straw application rates (0, S0; 5.310, S1; 10.620, S2 and 21.240 kg/ha, S3) to a purplish paddy field (Regosols in FAO taxonomy) with the static chamber technique. The seasonal accumulative CH4 (TCH4) or N2O emissions from S0, S1, S2 and S3 were 255, 417, 571 and 687 kg/ha or 3.22, 2.66, 2.35 and 2.16 kg/ha during period from June 1 to September 14, 2005, respectively. Seasonal accumulative CH4 emission was significantly correlated with straw application (Xstraw) (TCH4 = 290.72 + 0.02 Xstraw, r2 = 0.93, P < 0.05). Significantly positive linear correlation was displayed between CH4 flux rate and soil temperature at 5 cm depth (Tsoil) (P < 0.05, 18.0°C ≤ Tsoil ≤ 26.4°C). Straw application less than 5.300 kg/ha could enhance plant carbon fixation amounts, whilst both CH4, N2O emissions and the ratio of carbon equivalent emission to carbon fixation were not increased in the purplish paddy soil.